Rewriting the Italian novella in counter-reformation Spain - Rabell, Carmen (JSTOR EBA., 2003)
As they reshaped the Italian novella during the Counter-Reformation, Spanish narrators labelled their texts as exemplary. However, critics have usually agreed that there is a contradiction between the morals preached in the narrative frames, prologues and sententiae of Spanish novellas and the content of the plots. Rabell sees this ambiguity as a result of the use of the rhetoric of the fictitious case: Spanish novellas rewrite the Italian genre with the specific purpose of either challenging or validating the rules and regulations of Counter-Reformation Spain.